Sex Expression in Cucumber Plants as Affected by 2-Chloroethylphosphonic Acid, Ethylene, and Growth Regulators - Iwahori, Shuichi (1970)
The effects of 2-chloroethylphosphonic acid (Ethrel), ethylene, and some growth retardants on sex expression of cucumber plants (Cucumis sativus L.) were investigated, with the use of a monoecious cultivar (Improved Long Green) which has a strong tendency toward maleness. Ethrel caused increased femaleness when applied at 50 milligrams per liter at the first to the third leaf stage, but when applied at the cotyledon stage it was ineffective. The later the time of application, the higher the node at which the first female flower appeared. The total number of female flowers was about the same regardless of application time. A mixture of gibberellins A(4) and A(7) caused maleness, and Ethrel caused femaleness. However, when applied in combination at the first leaf stage the interaction was not significant. It seems, therefore, that Ethrel and gibberellins are not antagonistic but rather have different sites of action, although they have opposing effects on sex expression. Ethylene caused femaleness but was far less effective than Ethrel. Alar (N-dimethylaminosuccinamic acid), CCC((2-chloroethyl)trimethylammonium chloride), Phosphon D(2, 4-dichlorobenzyl-tributylphosphonium chloride), and abscisic acid did not affect sex expression of cucumber.